Hubungan Mutu Pelayanan Kesehatan dengan Tingkat Kepuasan Pasien Rawat Jalan di Poli Umum Puskesmas Kapan Kecamatan Mollo Utara Kabupaten Timor Tengah Selatan - Mega Inang Marsalina Sarata; Yoseph Kenjam; Yuliana Radja Riwu (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
The quality of health services is an important factor in the utilization of health services. Assessment of the quality of health services is not only on the physical recovery of diseases but also on the knowledge, attitudes, skills of officers when providing health services, communication, information, courtesy, punctuality, responsiveness and availability of adequate physical facilities and environments.  This study aims to analyze the relationship between the quality of health services and the level of outpatient satisfaction at the public poly Kapan Public Health Center, North Mollo District, South Central Timor Regency.  The quality of service analyzed includes the dimensions of physical evidence (tangible), reliability   (reliability), responsiveness (responsiveness), assurance (assurance) and empathy   (empathy).  This type of research is quantitative with an analyticalde science survey using a cross sectional design. The study sample amounted to 94 patients taken using a simple random sampling technique. Data analysis using chi square test  with significance level of 5%. The results showed arelationship between the quality of health services and the level of patient satisfaction based on the dimensions of physical evidence (tangible) p=0.001, dimensions  of reliability (reliability) p=0.008, dimensions of responsiveness p=0.001, dimensions of assurance (assurance) p=0.000 and    dimensions empathy p=0.001 in patients treated at the general poly Kapan Public Health Center, North Mollo District, South Central Timor Regency.